Social Transformation Through Non-Formal Education: Implementing Paulo Freire’s Critical Values - Arsyad, Yolandika; Asri, Muhammad; Febriansa, Febriansa (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to evaluate Paulo Freire's theory of education for liberation within the context of non-formal education in Indonesia. Freire's theory, emphasizing the importance of critical consciousness, dialogue, and the active role of learners in the educational process, serves as a conceptual foundation for designing emancipatory educational practices, particularly for marginalized groups. Employing a literature review method, this research examines studies relevant to Freire's ideas and their implementation in non-formal education, especially community-based approaches oriented towards community empowerment. The analysis reveals that applying Freire's critical education principles can strengthen learners' positions as subjects in the learning process and promote social transformation through contextual and participatory education. These findings recommend the development of non-formal education models that are more reflective, dialogical, and rooted in the learners' social realities, as efforts toward transformative and inclusive education.